Plasma antibodies to oral bacteria and risk of pancreatic cancer in a large European prospective cohort study. - Michaud, D; Izard, J; Wilhelm-Benartzi, C; You, D; Grote, V; Tjønneland, A; Dahm, C; Overvad, K; Jenab, M; Fedirko, V; Boutron-Ruault, M; Clavel-Chapelon, F; et al. (2013)
OBJECTIVE: Examine the relationship between antibodies to 25 oral bacteria and pancreatic cancer risk in a prospective cohort study. DESIGN: We measured antibodies to oral bacteria in prediagnosis blood samples from 405 pancreatic cancer cases and 416 matched controls, nested within the European Prospective Investigation into Cancer and Nutrition study. Analyses were conducted using conditional logistic regression and additionally adjusted for smoking status and body mass index. RESULTS: Individuals with high levels of antibodies against Porphyromonas gingivalis ATTC 53978, a pathogenic periodontal bacteria, had a twofold higher risk of pancreatic cancer than individuals with lower levels of these antibodies (OR 2.14; 95% CI 1.05 to 4.36; >200 ng/ml vs ≤200 ng/ml). To explore the association with commensal (non-pathogenic) oral bacteria, we performed a cluster analysis and identified two groups of individuals, based on their antibody profiles. A cluster with overall higher levels of antibodies had a 45% lower risk of pancreatic cancer than a cluster with overall lower levels of antibodies (OR 0.55; 95% CI 0.36 to 0.83). CONCLUSIONS: Periodontal disease might increase the risk for pancreatic cancer. Moreover, increased levels of antibodies against specific commensal oral bacteria, which can inhibit growth of pathogenic bacteria, might reduce the risk of pancreatic cancer. Studies are needed to determine whether oral bacteria have direct effects on pancreatic cancer pathogenesis or serve as markers of the immune response.